1999
DOI: 10.1136/bjo.83.5.514
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for strabismus in children born before 32 weeks' gestation

Abstract: Aim-To investigate risk factors associated with strabismus in children born prematurely. Methods-Prospective study of all children born before 32 weeks' gestation between 1 January 1990 and 31 December 1991 in a geographically defined population of approximately 3 million in the Northern Region of the United Kingdom. All children were examined aged 2 years by the same ophthalmologist and paediatrician. Results-558 children (98.6% of study group) were examined. Logistic regression showed an increased risk of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
1
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 19 publications
1
50
1
2
Order By: Relevance
“…This issue has been addressed in a number of studies by multifactorial analysis; however, the risk factors identified include cicatricial ROP, refractive error, family history, birth weight, anisometropia, maternal age, smoking, ethnic origin, and general development quotient, with all factors being independently associated with strabismus. 41,42,44,50 This considerable disparity in risk factors highlights the complexity of identifying those children at greatest risk of developing strabismus.…”
Section: Strabismusmentioning
confidence: 99%
See 1 more Smart Citation
“…This issue has been addressed in a number of studies by multifactorial analysis; however, the risk factors identified include cicatricial ROP, refractive error, family history, birth weight, anisometropia, maternal age, smoking, ethnic origin, and general development quotient, with all factors being independently associated with strabismus. 41,42,44,50 This considerable disparity in risk factors highlights the complexity of identifying those children at greatest risk of developing strabismus.…”
Section: Strabismusmentioning
confidence: 99%
“…There is no disputing the increased prevalence of strabismus in the low birth weight population compared to children born at term, [40][41][42] but the pattern of development and aetiology are less clear.…”
Section: Strabismusmentioning
confidence: 99%
“…[1][2][3][4][5] Strabismus can cause abnormal binocularity and amblyopia, necessitating amblyopia therapy, spectacle wear, and/or surgical procedures. 6 Additionally, there may be psychosocial consequences from the cosmetic effect of misaligned eyes.…”
mentioning
confidence: 99%
“…There is no doubt about the greatest prevalence of strabismus in premature children compared to those born at term, although the etiological process is not very clear. There are several studies that show the association between prematurity and born of low weight (<2500 g) and strabismus, probably due to lack of maturity of the cortical areas related to vision and eye movements, despite the mechanisms [10][11][12][13][14] . In active or passive maternal smoking, there was also no significant association to ET (p=0.50) or XT (p=0.32).…”
Section: Discussionmentioning
confidence: 99%